The new carbon architecture : building to cool the climate - King, Bruce (Structural engineer) (desLibris. Books collection., 2017)
"It's time to move past "green buildings," which alone aren't enough to halt climate change. The New Carbon Architecture explores how biomimicry-inspired innovations in architecture and construction--from cities made of wood to insulation grown from straw and mycelium--will pull carbon from the atmosphere, heal the climate, and produce safer, healthier, and more beautiful buildings."--